Impact of Climate Change on Rice and Wheat Adaptation Strategies and resource conservation measures - Prakash, Ved; Kumar, Santosh; Dwivedi, S K; Mishra, J S (Indian Farming, 2017)
Climate change and increase in temperature over the years hasadverse effect on rice and wheat crops. It is therefore necessary tofollow adaption strategies and resource conservation measures forgrowing these crops.